Remote preconditioning as a novel "conditioning" approach to repair the broken heart: potential mechanisms and clinical applications - Ravingerova, T; Farkasova, V; Griecsova, L; Carnicka, S; Murarikova, M; Barlaka, E; Kolar, F; Bartekova, M; Lonek, L; Slezak, J; Lazou, A (Physiological research, 2016)
Remote ischemic preconditioning (RIPC) is a novel strategy of protection against ischemia-reperfusion (IR) injury in the heart (and/or other organs) by brief episodes of non-lethal IR in a distant organ/tissue. Importantly, RIPC can be induced noninvasively by limitation of blood flow in the extremity implying the applicability of this method in clinical situations. RIPC (and its delayed phase) is a form of relatively short-term adaptation to ischemia, similar to ischemic PC, and likely they both share triggering mechanisms, whereas mediators and end-effectors may differ. It is hypothesized that communication between the signals triggered in the remote organs and protection in the target organ may be mediated through substances released from the preconditioned organ and transported via the circulation (humoral pathways), by neural pathways and/or via systemic anti-inflammatory and antiapoptotic response to short ischemic bouts. Identification of molecules involved in RIPC cascades may have therapeutic and diagnostic implications in the management of myocardial ischemia. Elucidation of the mechanisms of endogenous cardioprotection triggered in the remote organ could lead to the development of diverse pharmacological RIPC mimetics. In the present article, the authors provide a short overview of RIPC-induced protection, proposed underlying mechanisms and factors modulating RIPC as a promising cardioprotective strategy.
Keywords: Ischemic Preconditioning, Myocardial; reperfuzní poškození myokardu; Animals; Humans; Myocardial Reperfusion Injury; ischemické přivykání; lidé; zvířata